PREVALENCE AND INTENSITY OF GASTROINTESTINAL PROTOZOAN INFECTION IN BALINESE CATTLE CALVES AT BERINGKIT ANIMAL MARKET, BADUNG REGENCY - Iwan Ramdani; Nyoman Adi Suratma; Sri Kayati Widyastuti (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Bali cattle are one of the indigenous cattle breeds in Indonesia that are the direct result of domestication from wild bulls. Gastrointestinal protozoan infection is still a factor that often disturbs the health of bali cattle. This study aimed to determine the prevalence and intensity of gastrointestinal protozoa infection in bali calves breeds in Beringkit Animal Market, Badung Regency. The examination was conducted using the floating method, with fecal samples from 100 bali cattle seedlings and the Mc Master method to determine protozoan infection. The results found 41% of the samples were infected with gastrointestinal protozoa. Based on gender, the prevalence of gastrointestinal protozoa infection in male bali calves was 41.1% and in female bali calves was 40.9%. The types of gastrointestinal protozoa found were Eimeria sp, and Balantidium sp. The average infection intensity of Eimeria sp, 36% with an infection intensity of 622.5 ± 2359.21 oocysts/gram of feces, and Balantidium sp, 17% with an infection intensity of 58.82 ± 75.99 cysts/gram of feces. The prevalence in this study was moderate. Male and female cattle have the same chance of being infected with gastrointestinal protozoa. The average infection intensity of Eimeria sp, and Balantidium sp, both protozoa were mild. It is recommended to improve environmental sanitation around bali breeding calves, routine feces cleaning and hygienic feeding methods